IMPROVING PEDAGOGICAL TECHNOLOGIES FOR PREPARING YOUNG STUDENTS FOR SMALL BUSINESS - Fayzullaev Ulugbek Tursunboyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2021)
To determine the influence of exogenous (external), endogenous (internal) factors on business education by preparing students for entrepreneurship in this area of pedagogy, increasing their economic knowledge and financial literacy; - to define and classify the concepts of "small business", "business", "entrepreneurship", to define the basic concepts of preparing students for small business and private entrepreneurship - to determine the pedagogical and psychological characteristics of increasing students' interest in business and entrepreneurship; generalization of effective teaching experience in this area, development of a didactic model on its basis; - to substantiate the need for cooperation between educational institutions and families, youth organizations, as well as experienced entrepreneurs in preparing students for doing business, to develop recommendations and proposals for identifying promising areas; -improvement of the mechanism for organizing interactive lessons based on problem solving, research, analysis of hypothetical situations, business games, development of a business training program to prepare students for entrepreneurship based on educational projects.